1973
DOI: 10.1128/aac.4.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Cytarabine in Herpesvirus–Infected Rats

Abstract: Intranasal inoculation of herpesvirus (approximately 1.8 mean lethal doses [LD 50 ] in 0.1 ml) into 105- to 115-g rats produces paralytic disease in 4 to 5 days and 80 to 100% mortality in 8 to 12 days. Cytarabine (ara-C) (40 to 320 mg/kg), administered subcutaneously to inoculated rats, delays the onset of paralysis and protects the animals from death. Drug treatments were given twice daily for 5 days. Beneficial drug effects were observed even when initiation of therapy was delayed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It is also possible that another viral gene product, such as ORF 36, the virus phosphotransferase homologue of human CMV UL97, can phosphorylate GCV and be responsible for its activity in vivo (4). Alternatively, because of GCV superior toxicity, preferential uptake into rapidly growing tumor cells and conversion by cellular enzymes may create a situation where GCV acts as a chemotherapeutic reagent, similar to other nucleoside analogs, such as cytosine arabinofuranoside and adenine arabinofuranoside, that have both antiviral and chemotherapeutic activity (1,35,37,50).…”
Section: Hhv8 Orf 21 Has Tk Activity In Mammalian Cells To Determinementioning
confidence: 99%
“…It is also possible that another viral gene product, such as ORF 36, the virus phosphotransferase homologue of human CMV UL97, can phosphorylate GCV and be responsible for its activity in vivo (4). Alternatively, because of GCV superior toxicity, preferential uptake into rapidly growing tumor cells and conversion by cellular enzymes may create a situation where GCV acts as a chemotherapeutic reagent, similar to other nucleoside analogs, such as cytosine arabinofuranoside and adenine arabinofuranoside, that have both antiviral and chemotherapeutic activity (1,35,37,50).…”
Section: Hhv8 Orf 21 Has Tk Activity In Mammalian Cells To Determinementioning
confidence: 99%
“…Renis (28) demonstrated that ara-C treatment of rats inoculated intranasally with herpesvirus delayed the onset of paralysis and death, reduced final mortality, and delayed and suppressed viral replication in brain tissue. corneal scarification method and treated with ara-C. ara-A has been shown to be effective in the treatment of HVH keratitis (30) and subsequent encephalitis (29) in hamsters.…”
Section: 0-mentioning
confidence: 99%
“…Myelocytomatosis virus is a retrovirus, which is an enveloped, negative-sense, single-stranded RNA virus, whereas Rous sarcoma virus is an enveloped, positive-sense, single-stranded RNA virus. Although there are no studies showing that cytarabine is effective against infection of an RNA virus, one report demonstrated that cytarabine can affect DNA virus infection [12]. Pyrogallol was reported to have anti-virus effects on human influenza virus strain A/Udorn/72, avian influenza virus A/swan/Shimane/499/83, herpes simplex virus-1, vesicular stomatitis virus, and retrovirus [13].…”
Section: E Drug Discoverymentioning
confidence: 99%